The Racah algebra for groups with time reversal symmetry. III - Newmarch, J.D.; Golding, R.M. (AIP Publishing, 1983)
The coupling of basis vectors and the recoupling of irreducible corepresentations is considered. The difference between the coupling coefficient and 3jm tensors leads to a variety of 6j and recoupling tensors.